THE EFFECT OF GROUP COUNSELING USING DHIKR THERAPY TO REDUCE AGGRESSIVE BEHAVIOR IN DRUG ADDICTS - Sampurna, Annisa Salsabilla Ratu; Mulyani, Mirna Ari; Putra, Bela Janare (LP2M IAI Al-Khairat Pamekasan, 2025)
Drug abuse is often associated with increased aggressive behavior. Aggressive behavior in drug addicts can vary, from verbal aggression to physical violence. Factors such as the type of drug used, the individual's mental condition, and the social environment can affect the level of aggression shown. Therefore, this study aims to analyze the effect of group counseling using dhikr therapy to reduce aggressive behavior in drug addicts. This study uses quantitative writing with the Pre-Experiment method with the One-Group Pretest and Posttest type with the Purposive Sampling technique, and researchers use numbers processed in SPSS 26. Based on the research conducted, the pretest results showed an average mean value of 77 which was categorized as high, then given treatment through group counseling with dhikr therapy for four meetings after which a posttest was given to determine whether there was an effect after being given treatment with an average mean value of 46.1 which could be categorized as low. And based on the results of the statistical test output, the T test results were obtained with a significant value (2-tailed) of 0.000 <0.05, it can be concluded that